Carboxylated fullerenes: Physico-chemical properties and potential applications. (December 2017) - Semenov, Konstantin N.; Andrusenko, Elena V.; Charykov, Nikolai A.; Litasova, Elena V.; Panova, Gayane G.; Penkova, Anastasia V.; Murin, Igor V.; Piotrovskiy, Levon B.
Abstract: Carboxylated fullerenes may have wide applications in science and technology. Therefore, there is particular interest in investigating the physico-chemical and biological properties and the applications of these compounds. This review systematizes the current literature data on the synthesis, physico-chemical properties and application of carboxylated fullerenes as nanomodifiers of polyelectrolytes as well as their use in medicine and agriculture. Presented experimental and theoretical data gives a comprehensive overview of these substances and can be valuable to specialists in the fields of nanotechnology, nanomaterials and bionanomedicine.